Two new species of fanged frogs from Peninsular Malaysia (Anura: Dicroglossidae) - Matsui, Masafumi; Belabut, Daicus M.; Ahmad, Norhayati (Zootaxa, 2014)
Taxonomic status of fanged frogs from the Peninsular Malaysia, previously assigned to Limnonectes kuhlii, is assessed using genetic and morphological approaches. Phylogenetic relationships inferred from sequences of the mitochondrial and nuclear genes revealed that the fanged frogs from the Peninsula form a monophyletic group and are clearly divergent from other species previously, or even now, assigned to L. kuhlii from Mainland Southeast Asia. In both mtDNA and nuDNA phylogeny, the Malay Peninsula clade diverges into two lineages, one from north (Larut Hill, Perak, and Hulu Terengganu, Terengganu) and another from south (Genting Highlands, Pahang, and Gombak, Selangor). These lineages are separated by large genetic distances, comparable with those observed between some other species of L. kuhlii-like frogs. Although the two lineages are very similar morphologically, they are distinguishable in several morphological traits and are considered heterospecific. We therefore describe them as L. utara sp. nov. and L. selatan sp. nov. These new species differ from all other species of kuhlii-like frogs from Mainland Southeast Asia by the surface of tibia, which is densely covered by large warts.